CONSERVATION CRIME AND PANGOLIN POACHING: TENSIONS BETWEEN CUSTOMARY USE AND CONSERVATION LAW (The Pretoria Student Law Review, 2021)
In this paper, the author assesses the interplay between African customary use of pangolin and conservation law and to what extent the existing legislative framework undermines the heritage value of pangolins for customary communities. The author discusses the extent to which the laws governing pangolin protection in South Africa impose limitations on the customary use of pangolin for customary communities. Finally, the author considers whether customary law rights of access to and use of pangolin can or ought to coexist with conservation law. This paper aims to illustrate that the conservation laws regulating pangolin in South Africa impose excessive limitations on customary use and access to pangolin.
Keywords: pangolin; pangolin poaching; conservation crime; customary communities; customary use